Flexible Working Space and Organizational Culture on Employee Work Productivity - Razak, Nurlaely; Faturrahman, Muh.; Cahya, Nur; Tafsir, Muh. (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the effect of Flexible Working Space on Employee Work Productivity at PT. Pelabuhan Indonesia (Persero) Regional 4. The development of technology and the dynamics of the work environment encourage organizations to implement a more flexible workspace concept to improve work effectiveness and efficiency. The research method used is quantitative with an associative approach. Data was collected by distributing questionnaires to employees and analyzed using simple linear regression. The study results indicate that Flexible Working Space has a positive and significant effect on Employee Work Productivity, with a regression coefficient value of 0.244 and a significance value of 0.000 (<0.05). This indicates that the implementation of flexible workspace can increase employee comfort, independence, and work motivation, which directly impacts productivity. This finding aligns with several previous studies emphasizing flexibility's importance in creating an adaptive and productive work environment. However, work flexibility also needs to be balanced with proper management to avoid the risk of decreasing work coordination and accountability.